Euglycemic Diabetic Ketoacidosis With COVID-19 Infection in Patients With Type 2 Diabetes Taking SGLT2 Inhibitors - Vitale, Rebecca J. (AACE Clin Case Rep, 2020)
OBJECTIVE: Diabetes mellitus is associated with poor outcomes in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Diabetic ketoacidosis (DKA) has also been reported to occur with this virus. A cluster of cases of euglycemic DKA (euDKA) was identified in patients with type 2 diabetes mellitus using sodium-glucose cotransporter-2 inhibitors (SGLT2is) who developed SARS-CoV-2 infection. METHODS: The cases were identified by the authors while providing clinical care, and details were collected. RESULTS: Five cases of euDKA, presenting with glucose levels <300 mg/dL, were identified over the course of 2 months by the endocrinology consult service. All patients had a history of type 2 diabetes mellitus with no known history of DKA. All were taking SGLT2is. Oral antihyperglycemic medications were stopped for all patients on admission. All received intravenous insulin infusion to treat DKA before being transitioned to a subcutaneous insulin regimen. SGLT2i use was discontinued for all patients who were discharged. CONCLUSION: EuDKA has been seen in the setting of acute illness in patients using SGLT2is, but this cluster of cases suggests that there is a specific association with SARS-CoV-2 infection. In addition to the known risk of euDKA with SGLT2i use, coronavirus disease 2019-specific mechanisms may include a direct toxic effect of the virus on the pancreatic islets, an accelerated inflammatory response promoting ketosis, and the diuretic effect of SGLT2i in conjunction with anorexia and vomiting. It is crucial to counsel patients to stop SGLT2is when sick, especially if SARS-CoV-2 infection is suspected.